Karakter Disiplin dalam Membangun Self Regulation Learning Siswa di SMAN 2 Palangka Raya - Aysah, Nurul; Muslimah, Muslimah; Hidayati, Sri (Jurnal Ilmiah Global Education, 2025)
This study aims to analyze the role of disciplinary character in building student self-regulation learning in Islamic Religious Education (PAI) learning at SMAN 2 Palangka Raya. Using a descriptive qualitative approach, this study involved 1 PAI teacher, 8 students who met the learning discipline criteria, and supporting informants in the form of BK teachers and student waka in class X-6. Data collection techniques were carried out through interviews, observations, and documentation, then analyzed using the Miles and Huberman interactive analysis model. The results of the study show that the character of discipline has a fundamental role in building students' self-regulation learning. From observations of learning discipline indicators according to Arikunto, which include attendance, attention during learning, assignment completion, and completeness of learning equipment, 8 students were found who met all learning discipline criteria. These students showed better ability to manage time, monitor the learning process, and evaluate academic achievement independently in accordance with the characteristics of self-regulation learning presented by Yong-Chil. The example of PAI teachers who are consistent in demonstrating disciplined behavior, combined with structured learning strategies such as weekly lesson planning systems, learning reflection journals, and active learning techniques, has proven effective in integrating the three phases of self-regulation learning according to Zimmerman, namely planning, monitoring, and evaluation. However, the study also identified both internal inhibiting factors such as time management difficulties and lack of metacognitive awareness, as well as external factors such as an unconducive learning environment and lack of social support. This study concludes that although the character of discipline plays an important role in building self-regulation learning, the process requires comprehensive support from teachers, families, and the education system to achieve optimal outcomes in PAI learning.